Bioactive contents and free radical scavenging activity of Moringa oleifera leaf extract under different storage conditions - Boonyadist Vongsak (2018)
Moringa oleifera Lam. (Moringaceae) possesses therapeutic potential for pharmaceutical product development. However, reports on chemical and biological stabilities of the bioactive components in the leaf extracts of M. oleifera are limited. This investigation aimed to evaluate the stability of bioactive compounds and free radical scavenging abilities of the leaf extracts stored under different conditions as established in the ASEAN guideline on drug stability study. The quantitative analysis of three major anti-oxidative constituents, crypto-chlorogenic acid, isoquercetin and astragalin, were performed using high-performance liquid chromatography. Total phenolics and total flavonoids contents, and DPPH free radical scavenging activity of the stored extracts were also investigated. After six months of storage, the bioactive contents and free radical scavenging activity of the extract kept at 25. ±. 2. °C with 60. ±. 5% relative humidity (RH) slightly decreased. About 50% decrease on the contents of active compounds and scavenging activity were found in the extract kept under accelerated condition at 40. ±. 2. °C with 75. ±. 5% RH. High temperature and humidity negatively impacted the contents of bioactive constituents and free radical scavenging activity of the extracts. Thus, the extracts and product from M. oleifera leaves should be kept in a cold place to prevent significant changes in chemical, physical and biological properties. © 2013 Elsevier B.V.